Dual Effect of Taxifolin on ZEB2 Cancer Signaling in HepG2 Cells - Dostál, Zdeněk; Sebera, Martin; Srovnal, Josef; Staffova, Katerina; Modriansky, Martin (Molecules, 2021)
Polyphenols, secondary metabolites of plants, exhibit different anti-cancer and cytoprotective properties such as anti-radical, anti-angiogenic, anti-inflammation, or cardioprotective. Some of these activities could be linked to modulation of miRNAs expression. MiRNAs play an important role in posttranscriptional regulation of their target genes that could be important within cell signalling or preservation of cell homeostasis, e.g., cell survival/apoptosis. We evaluated the influence of a non-toxic concentration of taxifolin and quercetin on the expression of majority human miRNAs via Affymetrix GeneChip™ miRNA 3.0 Array. For the evaluation we used two cell models corresponding to liver tissue, Hep G2 and primary human hepatocytes. The array analysis identified four miRNAs, miR-153, miR-204, miR-211, and miR-377-3p, with reduced expression after taxifolin treatment. All of these miRNAs are linked to modulation of ZEB2 expression in various models. Indeed, ZEB2 protein displayed upregulation after taxifolin treatment in a dose dependent manner. However, the modulation did not lead to epithelial mesenchymal transition. Our data show that taxifolin inhibits Akt phosphorylation, thereby diminishing ZEB2 signalling that could trigger carcinogenesis. We conclude that biological activity of taxifolin may have ambiguous or even contradictory outcomes because of non-specific effect on the cell.
Keywords: quercetin; signální transdukce; Hepatocytes; Cell Movement; buňky Hep G2; Quercetin; apoptóza; Primary Cell Culture; regulace genové exprese u nádorů; transkriptom; mikro RNA; polyfenoly; Signal Transduction; Cell Proliferation; primární buněčná kultura; Hep G2 Cells; transkripční faktor Zeb2; epitelo-mezenchymální tranzice; MicroRNAs; Transcriptome; Epithelial-Mesenchymal Transition; Polyphenols; Zinc Finger E-box Binding Homeobox 2; hepatocyty; Gene Expression; Humans; Gene Expression Regulation, Neoplastic; pohyb buněk; proliferace buněk; exprese genu; lidé; Apoptosis